STEM BUILD: An Online Community To Decrease Barriers to Implementation of Inclusive Tactile Teaching Tools - Melissa V. Ramirez (American Society for Microbiology, 2020)
Access to 3D printing and other “maker” technologies has opened new doors for the creation of classroom activities using physical models. Multiple strategies for implementing 3D-printed models exist, and work to define best practices is ongoing. We outline the strengths and weaknesses of common strategies for employing physical models in undergraduate biology courses and describe a novel strategy that we have developed to pair 3D-printed models with guided inquiry learning to create inclusive and interactive learning experiences. We further introduce the STEM BUILD website, a resource that we have developed to facilitate collaboration among instructors, makers, researchers, and Universal Design for Learning experts and reduce barriers to broad implementation of inclusive kinesthetic learning activities.